Hatchery Techniques For Black Tilapia (Oreochromis Niloticus) in Technical Implementation Unit–Freshwater Aquaculture Fisheries (UPT-PBAT Sukorejo), Malang Regency, East Java - Lilin Kurniawati; Lisa Elida; Siti Nur Kholissotin (IRDH International Journal of Technology, Agriculture and Natural Sciences, 2024)
Tilapia (Oreochromis niloticus) is an introduced fish popular in Indonesia because it has high nutritional and economic value. The Regional Government of Malang Regency through the Regency Fisheries Office Malang carried out tilapia hatchery activities which is one of the fish commodities. This research was conducted at the Technical Implementation Unit–Freshwater Aquaculture Fisheries (UPT-PBAT Sukorejo), Malang, East Java, Indonesia. This research was carried out from July 11, 2022 to August 31, 2022. The method used in this research was participatory. Method Participatory is a method that is carried out by involving the workforce as well as participants in all activities carried out to achieve a purpose The data collection method in the research included collecting primary data and secondary data. The hatchery technique of black tilapia consists of several stages Among them are egg-hatching techniques, larval maintenance, and seed maintenance black tilapia. In addition, the pond used in tilapia hatchery black water quality management, pest and disease checks, and business feasibility of the cultivation. Black tilapia (Oreochromis niloticus) hatchery carried out in UPT – Freshwater Aquaculture Fisheries (PBAT) Sukorejo, Malang. It was concluded that seeding was carried out naturally using the spawning with a ratio of 1 : 3. The number of male fish is 50 and the number of fish 150 females per pond. Obstacles and problems in fish hatchery black indigo (Oreochromis niloticus) in UPT – PBAT Sukorejo include the lack of Empty pond setup for spawning and seed keeping.